2001
DOI: 10.1097/00006534-200104010-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Accuracy of the Surgeonʼs Diagnosis and Significance of Positive Margins in Nonmelanoma Skin Cancers

Abstract: Even with a precise preoperative diagnosis, complete excision of nonmelanoma skin cancer is not always achieved. The conundrum remains the decision for appropriate secondary treatment. Many surgeons, regardless of the nature of the lesion, consider re-excision to be the only option. In a prior 4-year prospective study that ascertained the accuracy of our clinical diagnosis of skin lesions removed in an office setting, one-fifth were found to be malignant and 98 percent (n = 415) of the lesions were nonmelanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 19 publications
4
36
1
Order By: Relevance
“…8 Similarly, a study by plastic surgeons found that 16% of 414 nonmelanoma skin cancers had positive surgical margins. 9 Perhaps more significantly, a study by ophthalmologists on 141 primary periocular BCCs found that 52% of excised tumors had involved histologic margins. 10 This is in contrast to a more recent study demonstrating that excision of periocular BCCs with a 2-mm margin results in positive surgical margins in only 18% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similarly, a study by plastic surgeons found that 16% of 414 nonmelanoma skin cancers had positive surgical margins. 9 Perhaps more significantly, a study by ophthalmologists on 141 primary periocular BCCs found that 52% of excised tumors had involved histologic margins. 10 This is in contrast to a more recent study demonstrating that excision of periocular BCCs with a 2-mm margin results in positive surgical margins in only 18% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment is surgical removal and histological control of the margins. Even in cases of correct clinical diagnosis of a basal cell carcinoma preoperatively, the pathology report reveals positive margins in 16.2% of the cases (Hallock and Lutz, 2001). The overall recurrence rate after surgical removal is up to 10% (Schubert, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In a prospective trial on the correct diagnosis of non-melanoma skin cancer, the correct diagnosis of basal cell carcinoma was found only in 66.7% of the cases (Hallock and Lutz, 2001). It is particularly difficult to assess the tumour's expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Incisional biopsy of the lesion, for suspicion of both BCC and SCC is indicated when there is diagnostic uncertainty (8,9); it can be time consuming, costly and sometimes crippling and painful for the patient, not being justified in most cases (7). The accuracy of the NMSC clinical diagnosis is approximately 60.2% (20); in relation to BCC it ranges from 59% to 88.93% (18,(20)(21)(22)(23) and for SCC it ranges from 25% to 67.4% (18,(20)(21)(22)(23). The diagnostic accuracy presented in this study is within the variation observed in the literature for both BCC and SCC.…”
Section: Discussionmentioning
confidence: 99%
“…In different series, the percentage of surgical margins compromised by SCC ranges from 3.9% to 15% (22,26), with a recurrence rate ranging from 4% to 50% of the cases (20). According to a recent guideline (9), if the surgical margins are compromised by SCC (incomplete excision), it is essential the re-excision with a 4-6 mm safety margin, and if this is not feasible, adjuvant treatment (radiotherapy or chemotherapy) may be an acceptable option (9).…”
Section: Discussionmentioning
confidence: 99%